Supercritical Carbon Dioxide as a Green Alternative to Achieve Drug Complexation with Cyclodextrins - Mauro Banchero (Pharmaceuticals, 2021)
Cyclodextrins are widely used in pharmaceutics to enhance the bioavailability of many drugs. Conventional drug/cyclodextrin complexation techniques suffer from many drawbacks, such as a high residual content of toxic solvents in the formulations, the degradation of heat labile drugs and the difficulty in controlling the size and morphology of the product particles. These can be overcome by supercritical fluid technology thanks to the outstanding properties of supercritical CO2 (scCO2) such as its mild critical point, its tunable solvent power, and the absence of solvent residue after depressurization. In this work the use of scCO2 as an unconventional medium to achieve the complexation with native and substituted cyclodextrins of over 50 drugs, which belong to different classes, are reviewed. This can be achieved with different approaches such as the “supercritical solvent impregnation” and “particle-formation” techniques. The different techniques are discussed to point out how they affect the complexation mechanism and efficiency, the physical state of the drug as well as the particle size distribution and morphology, which finally condition the release kinetics and drug bioavailability. When applicable, the results obtained for the same drug with various cyclodextrins, or different complexation techniques are compared with those obtained with conventional approaches.